ADR mechanisms in european union maritime law - Çayhan, Elif Ekin (My University, 2009)
It has been experienced in the recent years that the use of Alternative Dispute Resolution increased rapidly world wide. European Union was sensitive to these innovations, as well. When the aim for sea trading and the economical needs considered all together with the former situation, it became necessary to complete this study. It is proved to be more logical resolving maritime disputes within Europe with ADR methods. The reasons for this subject matter to be chosen were the above mentioned condition and as well the desire to be able to enlighten the issue. The ADR Mechanisms in the European Union Maritime Law were told excluding Arbitration from the area, especially emphasizing on Mediation. Therefore, the study has been prepared and concluded in the manner that it would be useful for the Maritime and as a consequence for the Economy of the Union.

Dünyada son yıllarda Alternatif Uyuşmazlık Çözümüne başvuru artmıştır. Avrupa Birliğinin kendisine henüz yeni olan bu gelişmelere önem verdiği görülmektedir. Deniz ticaretine tekrar yönelmeler ile ekonomik ihtiyaçlar da göz önüne alındığında, bu çalışmanın tamamlanması gereklilik göstermiştir. Böylelikle Birlik içinde deniz ticaretine yönelik uyuşmazlıkların alternatif yöntemlerle çözümlenmesi daha mantıklı bir boyut kazanmıştır. Bu çalışmanın amacı yukarıda anılan gelişmelerin ortaya konulmasının yanı sıra konuya da ışık tutmaktır. Avrupa Birliği Deniz Ticareti Hukukunda Alternatif Yöntemler, Tahkimi ayrık tutarak, özellikle de Arabuluculuk vurgusu altında anlatılmıştır. Çalışma bu çerçevede, Birlik Deniz Ticaretine, dolayısıyla da Birlik Ekonomisine faydalı olmak üzere hazırlanıp, bitirilmiştir.
Keywords: Alternatif Uyuşmazlık Çözümü_Avrupa Birliği; Deniz Ticareti